Novel SCCmec type XV (7A) and two pseudo-SCCmec variants in foodborne MRSA in China. (19th January 2022) - Wang, Wei; Hu, Yue; Baker, Michelle; Dottorini, Tania; Li, Hui; Dong, Yinping; Bai, Yao; Fanning, Séamus; Li, Fengqin
Abstract: Background: Staphylococcal cassette chromosome mec (SCC mec ) elements are highly diverse and have been classified into 14 types. Novel SCC mec variants have been frequently detected from humans and animals but rarely from food. Objectives: To characterize a novel SCC mec type and two SCC mec variants identified from food-associated MRSA in China. Methods: Three MRSA (NV_1, NT_611 and NT_8) collected from retail foods in China were subjected to WGS and the SCC mec elements were determined. Results: The novel SCC mec XV identified in NV_1 carried the mec gene complex class A ( mecI-mecR1-mecA- IS 431 ) and the ccr gene complex 7 ( ccrA1B6 ), and a Tn 558 -mediated phenicol exporter gene fexA was detected in this SCC mec XV cassette. The pseudo-SCC mec elements ΨSCC mec NT_611 and ΨSCC mec NT_8 showed a truncated SCC mec pattern, carrying the class C2 mec gene complex but missing the ccr genes. The ΨSCC mec NT_611 element shared more similarities with those of Staphylococcus haemolyticus (AB478934.1) and carried a heavy metal resistance gene cluster cadD - cadX - arsC - arsB - arsR - copA . The ΨSCC mec NT_8 MRSA exhibited a highly resistant phenotype, showing the absence of a 19.3 kb segment compared with the reference SCC mec XII element (CP019945.1). Notably, a 46 kb region containing multiple transposons encoding antimicrobial or metal resistance genes flanked by IS 431 or IS 256 was identified ∼30 kb downstream from the mec gene complex in ΨSCC mec NT_8, which might explain such high resistance in MRSA NT_8. Conclusions: Our finding of novel and pseudo-SCC mec elements reflected the ongoing intra/interspecies genetic rearrangements in staphylococci. Further study will be needed to investigate the biological significance and prevalence of those SCC mec variants along the food chain.